Representasi Jurnalisme Investigasi sebagai Penegak Kebenaran dalam Film A Taxi Driver - Romanda Oktaviano; Aliasan .; Muslimin . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This scientific research was conducted to examine more deeply the representation of investigative journalism as an enforcer of truth in the film A Taxi Driver. The background of this study is the increasingly blurred nature of truth amid the rapid flow of information and the pressure exerted by those in power on the media, making it necessary to understand how investigative journalism is represented as an effort to reveal facts to the public. The film A Taxi Driver was chosen because it portrays the practice of investigative journalism during the 1980 Gwangju Uprising, a historical event rich in humanitarian values and courage. This study aims to analyze the representation of investigative journalism as an enforcer of truth in the film. The research employed a descriptive qualitative method with a text research approach. Data were collected through non-participant observation of film scenes, documentation analysis of dialogues, visuals, and narratives, as well as literature review. No respondents or informants were involved, as the study focused on media content analysis. The findings reveal that the film represents investigative journalism as a courageous, independent, and truth-oriented practice through the actions of journalists who strive to uncover facts concealed by those in power. Furthermore, the film highlights moral values, courage, and social responsibility as essential elements of the journalistic profession. In conclusion, A Taxi Driver portrays investigative journalism as a vital instrument in upholding truth and delivering factual information to society despite various risks and challenges